Prediction of Haul Units ' Requirements for the Open Pit Mines Operating Towards Closure - Salama, Abubakary (Tanzania Journal of Engineering and Technology, 2020)
The determination of haul units is one of the important steps in the equipment selection process. The process should aim at minimizing the operational costs and create an optimal match for the haulage system. When open pit mines operating towards closure, reducing the operational costs results in significant gaining, and the savings can be used to implement some of the closure plans. In this paper, the prediction of haul units for an open pit mine which operates towards the final pit limit was analysed using discrete event simulation and multiple linear regressions. The result shows that the changes in production rate have significantly impact on the number of haul units in operations. The obtained P-value suggests that there is a strong correlation between the haul units ' requirement, production rates, and haul distances. This reveals that the prediction of haul units ' requirements can be achieved using a developed regression model. It was observed that, the approach of using discrete event simulation and multiple linear regressions is useful in integrating fleet size decision in a multi-period production schedule. Keywords: Discrete event simulation, Haul unit selection, Mine closure, Multiple linear regression analysis, Open pit.